The diabetes care continuum in Venezuela: Cross-sectional and longitudinal analyses to evaluate engagement and retention in care - Goodman-Palmer, Dina; González-Rivas, Juan P; Jaacks, Lindsay M; Duran, Maritza; Marulanda, María Inés; Ugel, Eunice; Chavarro, Jorge E; Danaei, Goodarz; Nieto-Martinez, Ramfis (PLOS global public health, 2024)
The impact of the humanitarian crisis in Venezuela on care for noncommunicable diseases (NCDs) such as diabetes is unknown. This study aims to document health system performance for diabetes management in Venezuela during the humanitarian crisis. This longitudinal study on NCDs is nationally representative at baseline (2014-2017) and has follow-up (2018-2020) data on 35% of participants. Separate analyses of the baseline population with diabetes (n = 585) and the longitudinal population with diabetes (n = 210) were conducted. Baseline analyses constructed a weighted care continuum: all diabetes; diagnosed; treated; achieved glycaemic control; achieved blood pressure, cholesterol, and glycaemic control; and achieved aforementioned control plus non-smoking. Weighted multinomial regression models controlling for region were used to estimate the association between socio-demographic characteristics and care continuum stage. Longitudinal analyses constructed an unweighted care continuum: all diabetes; diagnosed; treated; and achieved glycaemic control. Unweighted multinomial regression models controlling for region were used to estimate the association between socio-demographic characteristics and changes in care continuum stage. Among 585 participants with diabetes at baseline, 71% were diagnosed, 51% were on treatment, and 32% had achieved glycaemic control. Among 210 participants with diabetes in the longitudinal population, 50 (24%) participants' diabetes management worsened, while 40 (19%) participants improved. Specifically, the proportion of those treated decreased (60% in 2014-2017 to 51% in 2018-2020), while the proportion of participants achieving glycaemic control did not change. Although treatment rates have declined substantially among people with diabetes in Venezuela, management changed less than expected during the crisis.